Keeping the balance: The noncoding RNA 7SK as a master regulator for neuron development and function. (29th May 2021) - Briese, Michael; Sendtner, Michael
Abstract: The noncoding RNA 7SK is a critical regulator of transcription by adjusting the activity of the kinase complex P‐TEFb. Release of P‐TEFb from 7SK stimulates transcription at many genes by promoting productive elongation. Conversely, P‐TEFb sequestration by 7SK inhibits transcription. Recent studies have shown that 7SK functions are particularly important for neuron development and maintenance and it can thus be hypothesized that 7SK is at the center of many signaling pathways contributing to neuron function. 7SK activates neuronal gene expression programs that are key for terminal differentiation of neurons. Proteomics studies revealed a complex protein interactome of 7SK that includes several RNA‐binding proteins. Some of these novel 7SK subcomplexes exert non‐canonical cytosolic functions in neurons by regulating axonal mRNA transport and fine‐tuning spliceosome production in response to transcription alterations. Thus, a picture emerges according to which 7SK acts as a multi‐functional RNA scaffold that is integral for neuron homeostasis. Abstract : The noncoding RNA 7SK serves as a platform for the control of transcriptional regulators and RNA‐binding proteins. Recently, 7SK functions in neuronal differentiation and axon growth were discovered. Dysregulation of 7SK‐interacting proteins can cause neurodevelopmental and ‐degenerative diseases, further implicating 7SK signaling pathways in neuron function and maintenance.